Ohmic Contact in 2D Semiconductors via the Formation of a Benzyl Viologen Interlayer. (2nd January 2019) - Yue, Dewu; Kim, Changsik; Lee, Kwang Young; Yoo, Won Jong
Abstract: The fabrication of a polymeric Ohmic contact interlayer between a metal and a 2D material using solution‐processed benzyl viologen (BV) is reported here. Predoping of the polymer alters the contact surface to obtain electron‐doped materials with ultrahigh work functions that significantly enhance the current density across the contact and reduce the contact resistance and Schottky barrier height. The fabrication of solution‐processed polymeric contacts for the preparation of high mobility MoS2, WSe2, MoTe2, and BP (black phosphorous) FETs with significantly lowered contact resistance is demonstrated. Ohmic contacts are achieved and produce 3‐, 700‐, 3000‐, and 17‐fold increases in electron mobilities, respectively, when the bottom gate voltage is 10 V compared to those respective materials alone. Ambipolar and p‐type 2D material based FETs could, therefore, be transformed into n‐type FETs. Most importantly, the devices exhibit excellent stability in both ambient and vacuum. Abstract : Solution‐processed polymeric contacts used in 2D semiconductor devices are reported here. Predoping of the benzyl viologen alters the contact surface to obtain electron‐doped materials with high work functions. Ohmic contacts are induced by the polymer and the thus formed devices produce 3‐, 700‐, 3000‐, and 17‐fold increases in the mobilities for MoS2, WSe2, MoTe2, and black phosphorus devices, respectively.